A Review of Ground Target Detection and Classification Techniques in Forward Scattering Radars - Kanona, M. E. A.; Hamza, M. G.; Abdalla, A. G.; Hassan, M. K. (Engineering, Technology & Applied Science Research, 2018)
This paper presents a review of target detection and classification in forward scattering radar (FSR) which is a special state of bistatic radars, designed to detect and track moving targets in the narrow region along the transmitter-receiver base line. FSR has advantages and incredible features over other types of radar configurations. All previous studies proved that FSR can be used as an alternative system for ground target detection and classification. The radar and FSR fundamentals were addressed and classification algorithms and techniques were debated. On the other hand, the current and future applications and the limitations of FSR were discussed.